Temperature-Dependent Growth of Geomyces destructans, the Fungus That Causes Bat White-Nose Syndrome - Verant, Michelle L. (Public Library of Science, 2012)
White-nose syndrome (WNS) is an emergent disease estimated to have killed over five million North American bats. Caused by the psychrophilic fungus Geomyces destructans, WNS specifically affects bats during hibernation. We describe temperature-dependent growth performance and morphology for six independent isolates of G. destructans from North America and Europe. Thermal performance curves for all isolates displayed an intermediate peak with rapid decline in performance above the peak. Optimal temperatures for growth were between 12.5 and 15.8°C, and the upper critical temperature for growth was between 19.0 and 19.8°C. Growth rates varied across isolates, irrespective of geographic origin, and above 12°C all isolates displayed atypical morphology that may have implications for proliferation of the fungus. This study demonstrates that small variations in temperature, consistent with those inherent of bat hibernacula, affect growth performance and physiology of G. destructans, which may influence temperature-dependent progression and severity of WNS in wild bats.